2018
DOI: 10.1038/s41588-018-0142-8
|View full text |Cite|
|
Sign up to set email alerts
|

Association analyses of more than 140,000 men identify 63 new prostate cancer susceptibility loci

Abstract: Genome-wide association studies (GWAS) and fine-mapping efforts to date have identified more than 100 prostate cancer (PrCa)-susceptibility loci. We meta-analyzed genotype data from a custom high-density array of 46,939 PrCa cases and 27,910 controls of European ancestry with previously genotyped data of 32,255 PrCa cases and 33,202 controls of European ancestry. Our analysis identified 62 novel loci associated (P < 5.0 × 10) with PrCa and one locus significantly associated with early-onset PrCa (≤55 years). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
718
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 733 publications
(760 citation statements)
references
References 63 publications
(63 reference statements)
17
718
1
5
Order By: Relevance
“…The risk region at 8q24 harbors multiple independent risk variants and is consistently recognized as the most significant PrCa risk region across ethnic populations. In our Latino men, it was associated with a 1.29-fold (95%CI: 1.19, 1.39) increased risk, which is similar to that reported in the largest European PrCa GWAS (OR = 1.23, 1.21, 1.25), 28 while larger than that reported in the AA PrCa GWAS (OR = 1.12, 95%CI: 1.07, 1.16). At 10q11.22, the risk variant rs10993994 has been consistently associated with PrCa risk across populations, [32][33][34] and is likely to be the putative causal variant within the region.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The risk region at 8q24 harbors multiple independent risk variants and is consistently recognized as the most significant PrCa risk region across ethnic populations. In our Latino men, it was associated with a 1.29-fold (95%CI: 1.19, 1.39) increased risk, which is similar to that reported in the largest European PrCa GWAS (OR = 1.23, 1.21, 1.25), 28 while larger than that reported in the AA PrCa GWAS (OR = 1.12, 95%CI: 1.07, 1.16). At 10q11.22, the risk variant rs10993994 has been consistently associated with PrCa risk across populations, [32][33][34] and is likely to be the putative causal variant within the region.…”
Section: Discussionsupporting
confidence: 85%
“…28,30 As found in previous studies in men of African ancestry, 16 directional consistency was also observed for the majority (>80%) of risk variants in Latinos, among which~30% were nominally statistically significant, suggesting that most of the known genetic susceptibility loci for PrCa generalize to the Latino population, which may not be surprising given their high degree of European ancestry. 28,30 As found in previous studies in men of African ancestry, 16 directional consistency was also observed for the majority (>80%) of risk variants in Latinos, among which~30% were nominally statistically significant, suggesting that most of the known genetic susceptibility loci for PrCa generalize to the Latino population, which may not be surprising given their high degree of European ancestry.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…P + T and LDpred models were trained and tested using the LDpred software (version 1.0.6) . The summary statistics from RPACTICAL meta‐analysis and an LD reference panel of 503 European samples from 1000 Genomes (Phase 3 version 5) were used. We fitted various P + T and LDpred models in the training population (placebo arm) to identify the best models based on the highest C‐statistic.…”
Section: Methodsmentioning
confidence: 99%
“…In prostate cancer (PCa), PRS based on well‐established risk‐associated SNPs has been consistently demonstrated to be an effective tool for PCa risk stratification. Higher percentiles of PRS scores and higher observed PCa risk have been reported in many study populations . In this study, we investigated the validity performance of PRS based on the GPS methods (P + T and LDpred) and compared it with GRS in two independent populations from an existing clinical trial cohort.…”
Section: Introductionmentioning
confidence: 99%